Digital primary care visits designed for different patient segments in the pre-pandemic era: A scoping review - Lakoma, Sanna; Pitkänen, Laura; Lahdensuo, Kaisa; Lillrank, Paul; Torkki, Paulus (Finnish Journal of eHealth and eWelfare, 2023)
Digital healthcare services have been implemented increasingly during and after the COVID-19 pandemic. They have been expected to improve access, reduce inefficiencies, improve the quality of care, lower the cost of healthcare, and provide more personalised care. This study focuses on digital visits: digital health care services that replace a general practitioner (GP) appointment in primary care. The aim of this review is to assess the perspectives used in studying digital visits, and to describe the services studied in terms of modalities used and patient segments targeted. We aim to find how digital visits were studied prior to their becoming a necessity during the COVID-19 pandemic. This is a scoping review of English language papers published between 1.1.2010-31.5.2020. The papers were eligible for the review if they focused on a digital primary care visit which replaced a face-to-face appointment with a GP. In total, 36 papers were included. Ten of the studies described services tailored to the needs of a patient segment. The rest of the studies (26/36) did not differentiate between patient segments. The most often-used perspective was that of the clinician (16/36 studies). Fifteen studies were descriptive. The costs and outcomes were rarely utilised as a perspective: the costs were used in only one study and outcomes in six. Patient experience was the perspective chosen in 11 studies. Among all the interventions, the most common modality was by phone call (20), and the second most common was asynchronous messaging and video consultation (10 each). Prior to the COVID-19 pandemic, digital visits had mostly been developed for the entire population instead of a particular segment of patients. We argue that developing them to fit the needs of a patient segment would help make them more acceptable and suitable for patients. More studies from the patient perspective are needed to develop these services to better fit the needs of patients. The situation is likely to have changed during the pandemic, as a large number of studies has been published since May 2020.